Probiotics, Prebiotics, and Synbiotics for the Prevention of Necrotizing Enterocolitis - Murphy, Kiera; Ross, R. Paul; Ryan, C. Anthony; Dempsey, Eugene M.; Stanton, Catherine (Frontiers in Nutrition, 2021)
Necrotizing enterocolitis (NEC) is a major cause of morbidity and mortality in preterm infants. The exact mechanism by which NEC develops is poorly understood however there is growing evidence to suggest that perturbations in the early-life gut microbiota composition increase the risk for NEC. Modulation of the gut microbiota with probiotics, prebiotics, or in combination (synbiotics) is an area which has attracted intense interest in recent years. In this narrative review, we present an overview of the role of the gut microbiota in the pathogenesis of NEC. We also examine the evidence currently available from randomized controlled trials, observational studies, systematic reviews, and meta-analysis examining the role of probiotics, prebiotics, and synbiotics in reducing the risk of or preventing NEC. Current clinical practice guidelines with recommendations on the routine administration of probiotics to preterm infants for NEC are also explored.